2023
DOI: 10.1055/a-2085-3964
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of early esophageal tumors in patients with cirrhosis or portal hypertension: a multicenter observational study

Abstract: Background: Liver cirrhosis and esophageal cancer share several risk factors, such as alcohol intake and overweight. Endoscopic resection is the gold standard treatment for superficial tumors. Portal hypertension and coagulopathy may increase the bleeding risk in these patients. This study aims to assess the safety and efficacy of endoscopic resection for early esophageal neoplasia in patients with cirrhosis or portal hypertension. Methods: This retrospective multicentric international study included consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…A systematic review and meta-analysis revealed that pooled rates of immediate & delayed bleeding, perforation, and death during EMR and/or ESD in patients with cirrhosis were 9.5% (CI 4.0-21.1), 6.6% (CI 4.2-10.3), 2.1% (CI 1.1-3.9) and 0.6% (CI 0.2-1.7), with only immediate bleeding rate higher than that in general population [22]. A multicenter observational study enrolled 134 early esophageal tumor lesions in 112 patients with liver cirrhosis reported 3(2.7%) perforations, 8 (7.1%) delayed bleedings, 8 (7.1%) sepsis, 6 (5.4%) cirrhosis decompensations within 30 days and 22 (19.6%) esophageal strictures [15]. A systematic review enrolling 68 gastric ESD patients reported a total of 8 (13.1%) post-ESD bleeding and 1 (1.6%) perforation [23].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A systematic review and meta-analysis revealed that pooled rates of immediate & delayed bleeding, perforation, and death during EMR and/or ESD in patients with cirrhosis were 9.5% (CI 4.0-21.1), 6.6% (CI 4.2-10.3), 2.1% (CI 1.1-3.9) and 0.6% (CI 0.2-1.7), with only immediate bleeding rate higher than that in general population [22]. A multicenter observational study enrolled 134 early esophageal tumor lesions in 112 patients with liver cirrhosis reported 3(2.7%) perforations, 8 (7.1%) delayed bleedings, 8 (7.1%) sepsis, 6 (5.4%) cirrhosis decompensations within 30 days and 22 (19.6%) esophageal strictures [15]. A systematic review enrolling 68 gastric ESD patients reported a total of 8 (13.1%) post-ESD bleeding and 1 (1.6%) perforation [23].…”
Section: Discussionmentioning
confidence: 97%
“…As for the management strategy of GOV, no consensus was reached. Either endoscopic or interventional therapy is acceptable for patients with early cancer of precancerous lesion far from GOV, While some researchers recommend against endoscopic treatment as it may induce submucosal fibrosis which will increase the technical difficulty of subsequent ESD [28,29], therefore transjugular intrahepatic portosystemic shunt (TIPS) or balloon-occluded retrograde transvenous obliteration were used to prevent variceal bleeding [15,[30][31][32]. Endoscopic radiofrequency ablation and laparoscopic-endoscopic cooperative surgery have also been reported for management of such patients [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12]. Although several studies have demonstrated that endoscopic treatments including ESD are safe and effective in this population [13][14][15][16][17][18][19][20], many concerns have not been solved satisfactorily or sometimes their conclusion was contradictory. Kim et al [14] found that liver cirrhosis was associated with a higher rate of cancer recurrence, while Choe et al [13] failed to demonstrate the difference regarding cancer recurrence rate, but they found the overall mortality rate was higher in the liver cirrhosis group.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [14] found that liver cirrhosis was associated with a higher rate of cancer recurrence, while Choe et al [13] failed to demonstrate the difference regarding cancer recurrence rate, but they found the overall mortality rate was higher in the liver cirrhosis group. Two recent studies have demonstrated that the presence of gastroesophageal varices (GOV) does not compromise the safety and efficacy of endoscopic resection [17,21]; however, the management of coexisting GOV remains debatable. What is more, no consensus was reached on many other concerns such as proper perioperative management, the minimum requirement of platelet (PLT) count, etc.…”
Section: Introductionmentioning
confidence: 99%